EITI as an Instrument of Fiscal Transparency and Accountability : A Case Study of Two FCV Countries - Cuvillier, Emmanuel F. (World Bank, Washington, DC, 2019)
Transparency and accountability in sector governance are basic and essential requirements to leverage the extractives (oil, gas, and mining) sector as an engine of economic growth in fragility, conflict, and violence (FCV) affected settings. Enabling them involves two vital steps. Transparency requires obtaining or publishing relevant and actionable data about sector governance. Accountability involves having the data to support responsible, efficient, and informed sector governance. Although several mechanisms exist to facilitate transparent data disclosures, the extractive industries transparency initiative (EITI) is the preeminent global standard to promote the open and accountable management of oil, gas, and mineral resources. This governance note presents a case study about how data disclosed through EITI has been effectively leveraged to support more transparent and accountable fiscal governance in two FCV countries - Afghanistan and Iraq.